Design of The High-Productivity of Coffee Cherry Processing Machine for Small Industry - Muhd Nor, Nik Hisyamudin; Ibrahim, Fakhrul Najwan (Research Progress in Mechanical and Manufacturing Engineering, 2023)
The coffee cherry processing machine is a tool used to facilitate the process to produce coffee beans. The processing of coffee cherries into coffee beans is highly complicated in various ways. This thesis project is carried out to design a high productive coffee cherry processing machine for a small industry. The time to complete the processing of coffee cherries will be taking more longer when using the manual peeling machine of the coffee cherry. The honey method can produce coffee beans that retain the aroma and flavor of the coffee is very suitable for this study. Therefore, this study aims to design automation of coffee cherry processing machine that benefits the small industry in Malaysia. Through this project, the productivity to produce the coffee has been shall be increased. The machine is designed based on small industry technical needs in terms of their specification of product. The design shall meet the necessary aspect such as sustainability, safety, maintenance, ergonomics, and functional performance. On the other hand, the selection of material and engineering design analysis shall be considered during the design phase to meet the requirement. George E. Dieter’s design process shall be referred to throughout the project design. The modeling and simulation of the product were done using Solidwork software to explain the detail of the concept of the product and all the dimensions of the components. The final design has an expected 803.7 kg/h of capacity and 95% efficiency. The estimation of the weight is 80.32kg with dimension 1324.5x534x1014. The selling price for the coffee cherry processing machine is RM 3,989.00.